Converting older apple trees into younger ones for quality fruits - Rao, V K; Sharma, S K (Indian Horticulture, 2015)
Rejuvenation can be very successfully done in old and senile apple orchards for obtaining a regular yield of quality fruits. The combination of proper canopy management with adequate nutrient management and timely management of insect pests and diseases, are prerequisites. By adopting these timely we can get quality fruits from old and senile orchards.